Precipitation behavior of MX phase in Cr-Mo-N-X(X=V,Nb,Ti) ferritic steels - Bae, D.S.; Jung, W.S.; Hong, K.T.; Lee, K.S. (Key Engineering Materials, 2007)
The precipitation behavior of MX nitrides during aging was investigated for Cr-Mo-N-X (X=V,Nb,Ti) ferritic steels. MX nitrides, which are finely dispersed in the matrix of Cr-Mo ferritic heat resistance steel, increase the creep strength of the steels by the precipitation strengthening mechanism. However, MX particles usually coarsen during aging, and this results in a decrease of creep strength. In order to clarify the coarsening process of MX particles, TEM samples were prepared from the aged for up to 3000hours specimens. During the aging, V, Nb and Ti containing nitrides (called MX nitrides) were precipitated out. From TEM observation, particle size distribution was confirmed and size distribution follows a typical log-normal distribution. The observed coarsening behavior well agreed with the calculated coarsening behavior of precipitates by Oswald ripening equation.